Production - Foreign - Petroleum Development in Africa - W. B. Heroy (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1931)
The rapid development of transportation routes on the African continent in recent years has greatly stimulated the demand for motor fuels and this in turn has led to more extensive exploration of such limited portions of the continent as seem to give promise of commercial oil production. In 1930, however, only two countries were classed as producers of petroleum and only one, Egypt, attained any importance. Egypt The petroleum production of Egypt is derived from the Gemsah and Hurghada fields on the west coast of the Red Sea and the Abu Durba, on its eastern shore in the Sinai peninsula. The Gemsah field, which began to produce commercially in 1912, has now practically ceased production, owing to the invasion of salt water. The Hurghada field has been producing since October, 1914. It now has about 60 producing wells. During 1929, a deeper sand with flowing produition was discovered in the eastern part of the field, producing oil of lighter gravity and free from water. The Abu Durba field was discovered by the exploration work of the Egyptian Government in 1918, oil having been found at a depth of 172 ft. This field has now 15 producing wells but a very small production. The production of these Egyptian fields over the last five years, is as follows: Metric Tons Metric Tons 1926......................... 172,881 1929....................... 271,520 1927......................... 184,557 1930....................... 277,146 1928......................... 269,324 This oil was all produced by the Anglo-Egyptian Oilfields Ltd., a constituent corporation of the Royal Dutch Shell group. During the year 1930 the Egyptian Government was engaged in geophysical prospecting of reserved areas along the Red Sea coast. Other Countries Soma1iland.—A geological survey of Somaliland was undertaken by the Somaliland Petroleum Co., Ltd., a subsidiary of the Royal Dutch